BINA DESA JADA BAHRIN MANDIRI BERBASIS PEMBERDAYAAN MASYARAKAT MELALUI KEGIATAN SIPIL SAHABAT DESA - Roby Hambali (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2015)
The new paradigm in the national education system mandated in Law Number 23 of 2003 is a local wisdom-based education unit that encourages the acceleration of development in the region based on the potential of local communities. The Department of Civil Engineering, Faculty of Engineering, Universitas Bangka Belitung as part of the education unit in question has the responsibility to carry out this mandate, which is outlined in the department's work program.The work program in question is the Bina Desa Mandiri program which is also the flagship program of the Faculty of Engineering, Universitas Bangka Belitung. In the Bina Desa Mandiri program, the Civil Engineering Department chose Jada Bahrin Village to be developed, especially in the field of infrastructure. The first activity with the theme "Sipil Sahabat Desa" was carried out in the even semester of the 2014/2015 academic year in the form of community service in structuring the area (cleanliness and tree planting), initiating a reading garden, health checks and treatment, blood donation, and socialization of healthy settlement sanitation. All of these activities are the first step in order to build community awareness in the management and development of Jada Bahrin Village infrastructure which is the target of the Independent Village of the Faculty of Engineering, Universitas Bangka Belitung.